Striatal dopamine release in a schizophrenia mouse model measured by electrochemical amperometry in vivo1. Issue 11 (7th June 2015) - Xu, Huadong; Zuo, Panli; Wang, Shirong; Zhou, Li; Sun, Xiaoxuan; Hu, Meiqin; Liu, Bin; Wu, Qihui; Dou, Haiqiang; Liu, Bing; Zhu, Feipeng; Teng, Sasa; et al.
<x xml:space="preserve">Abstract</x> This study demonstrated the unaltered dopamine release in the striatum in a schizophrenia model dysbindin−/− mice.